Assessment of solid waste management (SWM) practices in Pangkor Island Malaysia / Kok Weng Tan, Huoy Huoy Ong and Nor Hanisah Mohd Hashim - Kok, Weng Tan; Huoy, Huoy Ong; Mohd Hashim, Nor Hanisah (Faculty of Architecture, Planning and Surveying, 2016)
This study aimed to characterize recyclable and non-recyclable solid waste generation and identify the impacts of solid waste to the Pangkor island ecology. Methods used in this study were field investigation, opinion survey and domestic waste sampling. The data obtained from field sampling was analyzed by using reliability test (0.753), descriptive test, ANOVA single factor and Pearson Correlation Analysis. Through field investigation and sampling activity, the waste generated in Pangkor Island was found to be 0.34 kg/capita/day which slightly lower than Malaysian average waste generation of 1.3 kg/capita/day. Opinion survey and interview which included 34 items were conducted to local community for understanding; awareness and practice of local communities towards solid waste management (SWM). Result showed that total 34.0 % of respondents chose dumped solid waste into ocean, river or land. Only 43.6 % of respondents practiced recycling and composting in their own house. Result from Pearson Correlation analysis shows that knowledge of local communities towards SWM does not influence their attitude towards recycling (Pr > 0.05). Due to time restraints, language barrier, lack of numerators and expert’s opinion, the study did not carry out the field sampling in Malay and Indian communities in Pangkor Island which became major limitation for this study.